Hungarian Monitoring, 1 May 1989 . [Magyar rádiófigyelő], 1989. május 1 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Foreign correspondence on May 1 celebrations: Moscow, Prague, where many arrests made at counter-demonstration , Paris, Madrid, Rome Domestic Affairs: - May 1 parade, commemorations, speeches - National Council of Trade Unions (SZOT) general secretary Sándor Nagy supported reforms in his speech, but rejected fluster - National Council of Trade Unions (SZOT) youth council member Árpád Tatár declares: we need leaders whose can carry out their Monday statements on Tuesday - Károly Grósz's critical speech: the Party's leadership today cuts itself off from anything that would lead to a serious situation - Independent trade unions' spokesman emphasizes that workers again demand the "three eights": 8 hours work, rest and play - Károly Grósz and Mihály Jassó were guests at Népszabadság forum and answered questions on the state of János Kádár's health Külpolitika: - Külföldi beszámolók a május 1-i ünnepségekről: Moszkva , Prága, ahol több letartóztatásra is sor került egy ellentüntetés kapcsán - Párizs, - Madrid , Róma Belpolitika: - Május 1-i felvonulás, megemlékezések, beszédek - Nagy Sándor a SZOT főtitkára beszédében támogatta a reformokat, de elutasította a kapkodást - Tatár Árpád a SZOT ifjúsági tanácsa tagja kijelentette: olyan vezetőkre van szükség, akik hétfői mondanivalójukat kedden is vállalni tudják - Grósz Károly kritikus hangú beszédében kijelentette, a párt mai vezetése elhatárolja magát mindattól, ami e súlyos helyzethez vezetett - A független szakszervezetek szónoka hangoztatta, hogy a dolgozók ismét a "három nyolcast" követelik - Népszabadság Fórum vendége volt Grósz Károly és Jassó Mihály. A párt főtitkár Kádár János egészségi állapotával kapcsolatos kérdésre is válaszolt